STUDI PERUBAHAN KEDUDUKAN KELURAHAN DARI PERANGKAT DAERAH MENJADI PERANGKAT KECAMATAN DI KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU - Rahyunir, Muhammad Hafizh; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
In assisting in running the affairs of the concurrent government and general government affairs in the law on the local government, the Head of the Regency / Municipal Region is assisted by the regional apparatus of the kabupaten / kota. The juridical existence of the regional devices occurs between changes Law Number 23 Year 2014 with Law Number 32 Year 2004. Elements of Regional Apparatus pursuant to Article 120 paragraph (2) of Law Number 32 Year 2004 regarding Regional Government consists of; 1. Regional Secretariat, 2. Regional Offices, 3. Regional Technical Institutions 4. Regional Secretariat, and district. Therefore, it can be seen that the sub-district and kelurahan institutions are part of the regency / municipal apparatus, so the Camat and Lurah are directly responsible to the mayor This research was conducted in December 2016 until June 2017. The purpose of this research is to know the implementation of the change of the status of the kelurahan institution as a regional tool to be as a subdistrict device in Marpoyan Damai Sub-district, Pekanbaru City. The method used is qualitative descriptive method, where the researcher tries to explain the occurrence of change from the side of the working relationship of the Lurah and Camat, which until now is only coordinated to be superior and subordinate (Head of Sub-district becomes the direct superior of Lurah). Data collection techniques in this study is to use interviewing techniques and documentation. Based on interviews to all informants and based on supporting data and information obtained by researchers when conducting research. It can be concluded that the Status and Authority of the Village since the enactment of Law No. 23 of 2017 on Regional Government until the end of 2016 the status of urban village institutions remains as a regional tool, only since the beginning of 2017 the kelurahan status has changed into the kecamatan apparatus, Law Number 23 Year 2014 Regarding Pemerinrah area effectively in 2017 and the enactment of Regional Device Organizations (OPD) Local Government of Pekanbaru new cityKeywords: Local Government, Regional Device, Sub District Kelurahan